NATO : from regional to global security provider - Alexander, Yonah; Prosen, Richard (Lexington Books, 2015)
The book serves as a relevant and timely study of the most pressing issues facing NATO today - including recent lessons gained. It provides recommendations for consideration and further discussion (i.e., the "what" and the "how" regarding future policy options for the North Atlantic Alliance).